2015
DOI: 10.1089/dna.2015.2829
|View full text |Cite
|
Sign up to set email alerts
|

WISP3 (CCN6) Regulates Milk Protein Synthesis and Cell Growth Through mTOR Signaling in Dairy Cow Mammary Epithelial Cells

Abstract: The mTOR/S6K1 signaling pathway is the primary regulator of milk protein synthesis. While mTOR is known to be regulated at the translational level by amino acids, the mechanism by which mTOR accepts the amino acid signal is not yet clear. In this study, we describe the discovery of WISP3 as a potentially novel signaling factor that connects mTOR and amino acids. Treatment of dairy cow mammary epithelial cells with amino acids (lysine or methionine) increased both cell growth and the expression of β-casein (CSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…In dairy cattle, it was suggested that WISP3 is an important regulatory factor involved in the amino acid‐mediated regulation of milk protein synthesis and mammary epithelial cell growth (Jiang et al . ). Sebag et al .…”
Section: Summary Statistics For Body Weight At Tagging (Bwt) and At 2mentioning
confidence: 97%
“…In dairy cattle, it was suggested that WISP3 is an important regulatory factor involved in the amino acid‐mediated regulation of milk protein synthesis and mammary epithelial cell growth (Jiang et al . ). Sebag et al .…”
Section: Summary Statistics For Body Weight At Tagging (Bwt) and At 2mentioning
confidence: 97%
“…AA, particularly branched-chain AA, can participate in various cell physiological processes including cell growth, cell differentiation, cell metabolism, cell apoptosis and protein synthesis (Saxton and Sabatini, 2017). In DCMECs, AA are one of the most important regulatory factors for cell growth and lactation (Jiang et al ., 2015 a , 2015 b ). In this study, the cells were treated with different concentrations of AA, and the cell growth and casein synthesis were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The dairy cow mammary epithelial cells (DCMECs) were obtained from our lab (Jiang et al ., 2015 a , 2015 b ) and cultured with DMEM/F12 media (11320033, Gibco, California, USA) containing 10% fetal bovine serum (FBS, 16000044, Gibco) as previously report (Tong et al ., 2011). For the experiment, DCMECs were plated into 6 well plates with 1.0 × 10 5 cells per well and cultured with DMEM/F12 medium containing 10% FBS at 37 °C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, we have found that Kp-10 can promote CSN2 synthesis by activating GPR54.However, the exact molecular mechanism remains unclear, and so the next step is to detect the changes in downstream signals in the process. The CSN2 synthesis process is likely to include several participating signaling pathways, including ERK1/2, AKT, STAT, mTOR [ 6 , 19 , 20 , 40 , 41 ]. In addition, Kp-10 plays the role of an anti-metastasis agent via β-arrestin2/ERK by binding with GPR54 in human breast cancer cells [ 8 ].…”
Section: Discussionmentioning
confidence: 99%